Interactions between endocannabinoids and neurotrophins in adult neurogenesis : implications for spatial memory - Prenderville, Jack (Trinity College (Dublin, Ireland). Department of Physiology, 2014)
The cellular mechanisms underlying learning and memory have yet to be fully elucidated. Over the past fifteen years there has been a dramatic increase in the study of adult neurogenesis; a process in which neurons are generated from stem cells in the adult brain and which has been suggested to be relevant to learning and memory. This process has been confirmed in two areas of the adult brain, one being the dentate gyrus of the hippocampus, a brain region known to be important for learning and memory. The fact that neurogenesis occurs in this brain region throughout life has prompted many researchers to hypothesise that it may be a form of brain plasticity that is important for learning and memory. Exercise has been shown to be a potent enhancer of hippocampal-dependent memory and hippocampal plasticity, including neurogenesis.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin